Bibliometrics Analysis of Regional Autonomy Problem in Indonesia - iyomi hasti; Titin Purwaningsih (STI Policy and Management Journal, 2022)
This study looks for the relationship between studies on the problem of regional autonomy in Indonesia. The author uses VOSviewer to process data from the Scopus index journal for this report. VOSviewer was used in this study to process data and map the most common and most popular focus themes. The results showed that The last few years have shown the highest number of publications with 33 documents in 2019 and in 2020 the number of documents issued was 23 documents. Over the last few years, the comparison of the trends  is still dominated by Indonesia, which has 131 articles published in the Scopus database. Australia is in second place with a total of 27 published articles, followed by Singapore with 15 documents. VOSviewer analysis map classifies the largest nodes so that the most significant influence is environmental management. The drawback of this research is that the data source is only obtained from previous research so that further research can enrich data sources so that research results can be more accurate